(untitled) - Díaz, Tello Carlos (Historica Olomucensia, 2024)
The work reconstructs the history of the breakdown of the relationship between president Benito Juárez and general Porfirio Díaz in the Summer of 1867, after the victory of the Mexican Republic against the French Intervention and the Empire of Maximilian. At that time, the members of the liberal party divided themselves into two groups: those who were in favour of the re-election of Juárez and those who were against it, and the latter decided that their candidate would be Díaz, partly because he was the most popular general of the Republic, partly because he had shown to be an able administrator of the states under his command in the most populous part of Mexico. The methodology makes exhaustive use of primary sources, on the basis of academic literature published on the subject.
Keywords: Mexican history; Benito Juárez; Porfirio Díaz; Liberal party; Elections 1867; convocatoria